2020
DOI: 10.1002/ana.25743
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Mechanisms of Thalamic Pathology in Multiple Sclerosis

Abstract: Objective Thalamic atrophy is among the earliest brain changes detected in patients with multiple sclerosis (MS) and the degree of thalamic atrophy is a strong predictor of disability progression. The causes of thalamic atrophy are not fully understood. Here, we investigate the contributions of thalamic demyelinated lesions, thalamic neuronal loss, and cerebral white matter (WM) lesions to thalamic volume. Methods We used postmortem in situ magnetic resonance imaging (MRI) scans of 95 subjects with MS to corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 36 publications
7
50
0
Order By: Relevance
“…These findings add to the growing evidence that the two imaging findings may reflect different aspects of MS‐related brain injury 20 . More recently, a postmortem histologic‐imaging study by Mahajan et al has shown that thalamic volume atrophy may be better explained by WM lesions and subsequent afferent and efferent axonal/neuronal loss than thalamic demyelinating lesions, 26 a finding which may further explain our result.…”
Section: Discussionsupporting
confidence: 57%
“…These findings add to the growing evidence that the two imaging findings may reflect different aspects of MS‐related brain injury 20 . More recently, a postmortem histologic‐imaging study by Mahajan et al has shown that thalamic volume atrophy may be better explained by WM lesions and subsequent afferent and efferent axonal/neuronal loss than thalamic demyelinating lesions, 26 a finding which may further explain our result.…”
Section: Discussionsupporting
confidence: 57%
“…As non-lesioned brain volumes within six weeks after stroke are assumed to be similar to those before the stroke (Egorova et al, 2019), this finding suggests that larger thalamic volumes prior to stroke could provide a neuroprotective effect. Thalamic atrophy was recently associated with loss of extrinsic and intrinsic connectivity between the thalamus and the rest of the brain, suggesting that thalamic measures may serve as an index of global brain function (Mahajan et al, 2020). Future research using longitudinal datasets with greater spatial specificity could relate changes in specific thalamic nuclei to sensorimotor recovery to identify targets for neuroprotective or early stroke therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamic atrophy was recently associated with loss of extrinsic and intrinsic connectivity between the thalamus and the rest of the brain, suggesting that thalamic measures may serve as an index of global brain function. 26 Future research using longitudinal datasets with greater spatial specificity could relate changes in specific thalamic nuclei to sensorimotor recovery to identify targets for neuroprotective or early stroke therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamic lesions occur in two main types, subependymal or perivascular, and are present in 42-97% of patients (33)(34)(35). Imaging investigation in the thalamus have focused mainly on volumetric assessment (e.g., T1-or T2-weighted images, ultrahigh field) and overall measures of thalamic integrity [e.g., susceptibility-weighted imaging (SWI), magnetization transfer ratio (MTR), magnetic resonance spectroscopy, diffusion tensor imaging (DTI)].…”
Section: Imaging Of the Thalamus In Multiple Sclerosismentioning
confidence: 99%